PERSEPSI GURU DI SEKOLAH MENENGAH PERTAMA (SMP) PENYELENGGARA PENDIDIKAN INKLUSIF TERHADAP PEMBELAJARAN BAHASA INGGRIS BAGI SISWA TUNARUNGU DI KOTA PADANG - Dermayani - - (Universitas Negeri Padang, 2015)
This research was done due to a problem in several junior high schools as the organizers of inclusive education in Padang. The problem was that English learning was conducted classically with short learning hours. It was known that special need students required modifications in learning, particularly in language learning. The aim of research was to determine junior high school teachers’ perceptions as the operators of inclusive education toward English learning for deaf students in Padang. The design of this research was descriptive quantitative research. The technique of data collection were questionnaire and observation. The results showed that almost half (41.02%) of teachers perceived that deaf students were interested in participating in English learning. The teachers perceived that 11.1% of deaf students did not experience barriers fraction in learning Speaking while other 88.9% of them did have problems. In learning Listening, the teachers perceived that 5.3% of deaf students did not experience barriers fraction while other 94.7% of them did have problems. For the Writing aspect, the teachers perceived that 37.1% of deaf students did not experience barriers fraction while other 62.9% of them did have problems. Then, for the aspect of Reading, the teachers perceived that 33.9% of deaf students did not experience barriers fraction while other 66.1% of them did have problems. In terms of interaction, almost in part (38.88%) of deaf students were able to interact in the process of English learning with teachers and peers. Based on the results of this study, it was concluded that most of the teachers perceived that deaf students learned English by following the appropriate procedures both from the aspect of interest, barriers, and interaction.Keywords: teachers’ perceptions; teachers; inclusive; English; Deaf;